Finite element approximation of fractional Neumann problems. (7th September 2021) - Bersetche, Francisco M; Borthagaray, Juan Pablo
Abstract: In this paper, we consider approximations of Neumann problems for the integral fractional Laplacian by continuous, piecewise linear finite elements. We analyze the weak formulation of such problems, including their well-posedness and asymptotic behavior of solutions. We address the convergence of the finite element discretizations and discuss the implementation of the method. Finally, we present several numerical experiments in one- and two-dimensional domains that illustrate the method's performance as well as certain properties of solutions.